Validity of the MacDonald triad as a forensic construct: Links with psychopathology and patterns of aggression in sex offenders. (25th September 2020) - Joubert, David; Welsh, Kelsey; Edward, Lauren Joy
Abstract : Purpose: The MacDonald triad is composed of three developmental markers, including cruelty to animals, firesetting, and enuresis after the age of 5. Although there has been considerable interest in this construct initially, research has produced inconsistent results regarding its validity in terms of distinguishing between offender and non‐offender populations, or predicting future offences. The current study investigated the links between the triad, dimensions of psychopathology, and trajectories of aggression in a sample of 254 rapists previously collected from a single forensic mental health institution in the United States. Method: A retrospective temporal design was used to examine associations between variables in a sequence of ten offences. Results: Latent structure analyses yielded a two‐class solution for the triad indicators, a five‐dimensional model for psychopathology and three trajectories for the aggression variables over a sequence of ten offences. Univariate analyses revealed that the class characterized primarily by a high prevalence of cruelty to animals and firesetting was associated with a higher level of antisocial and aggressive traits, as well as with a trajectory of offending featuring higher levels of expressive aggression, at least during the first few offences in the sequence. These associations were large and weak‐to‐moderate in magnitude, respectively. Conclusions: If replicated, these findings may suggest that a particular subgroup of sex offenders showing components of the triad are at particular risk of developing antisocial features, thus impacting the level of risk they pose to potential victims and the community.